Physiological and Transcriptional Analyses Reveal Differential Phytohormone Responses to Boron Deficiency in Brassica napus Genotypes - Zhou, Ting; Hua, Yingpeng; Huang, Yupu; Ding, Guangda; Shi, Lei; Xu, Fangsen (Frontiers in Plant Science, 2016)
Phytohormones play pivotal roles in the response of plants to various biotic and abiotic stresses. Boron (B) is an essential microelement for plants, and Brassica napus (B. napus) is hypersensitive to B deficiency. However, how auxin responds to B deficiency remained a dilemma for many years and little is known about how other phytohormones respond to B deficiency. The identification of B-efficient/inefficient B. napus indicates that breeding might overcome these constraints in the agriculture production. Here, we seek to identify phytohormone-related processes underlying B-deficiency tolerance in B. napus at the physiological and gene expression levels. Our study indicated low-B reduced indole-3-acetic acid (IAA) concentration in both the shoots and roots of B. napus, and affected the expression of the auxin biosynthesis gene BnNIT1 and the efflux gene BnPIN1 in a time-dependent manner. Low-B increased the jasmonates (JAs) and abscisic acid (ABA) concentrations and induced the expression of the ABA biosynthesis gene BnNCED3 and the ABA sensor gene BnPYL4 in the shoot. In two contrasting genotypes, the auxin concentration decreased more drastically in the B-inefficient genotype ‘W10,’ and together the expression of BnNIT1 and BnPIN1 also decreased more significantly in ‘W10’ under long-term B deficiency. While the JAs concentration was considerably higher in this genotype, and the ABA concentration was induced in ‘W10’ compared with the B-efficient genotype ‘QY10.’ Digital gene expression (DGE) profiling confirmed the differential expression of the phytohormone-related genes, indicating more other phyohormone differences involving in gene regulation between ‘QY10’ and ‘W10’ under low-B stress. Additionally, the activity of DR5:GFP was reduced in the root under low-B in Arabidopsis, and the application of exogenous IAA could partly restore the B-defective phenotype in ‘W10.’ Overall, our data suggested that low-B disturbed phytohormone homeostasis in B. napus, which originated from the change of transcriptional regulation of phytohormones-related genes, and the differences between genotypes may partly account for their difference in tolerance (B-efficiency) to low-B.